2023
DOI: 10.3390/biology12020251
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Abnormal Lymph Nodes Detected with FDG-PET/CT in Suspected Vascular Graft Infection

Abstract: Vascular graft and endograft infections (VGEI) cause a serious morbidity and mortality burden. 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) imaging is frequently used in the diagnostic workup, but the additional value of abnormal (18F-FDG active and/or enlarged) locoregional lymph nodes is unknown. In this retrospective study, the additional diagnostic value of abnormal locoregional lymph nodes on 18F-FDG PET/CT imaging for VGEI was evaluated, including 54 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To increase diagnostic accuracy, a quantitative approach using focal uptake SUV max and dependent ratios has been introduced; however, studies evaluating VGEI patients and, specifically, comparisons to studies of non-VGEI patients are scarce [ 7 ]. Tsuda et al have suggested an aortic SUV max = 4.5 as a cut-off to diagnose VGEI, while v. Rijsewijk saw a mean SUV max = 9.5 vs. 5.4 in their VGEI-positive vs. VGEI-negative cohort [ 7 , 21 ]. Our analysis identified the SUV TLR with the highest diagnostic accuracy; however, our results showed an aortic SUV max (cut-off 6.45) and an SUV TBR with almost equally high sensitivity and specificity ( Figure 2 D, Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…To increase diagnostic accuracy, a quantitative approach using focal uptake SUV max and dependent ratios has been introduced; however, studies evaluating VGEI patients and, specifically, comparisons to studies of non-VGEI patients are scarce [ 7 ]. Tsuda et al have suggested an aortic SUV max = 4.5 as a cut-off to diagnose VGEI, while v. Rijsewijk saw a mean SUV max = 9.5 vs. 5.4 in their VGEI-positive vs. VGEI-negative cohort [ 7 , 21 ]. Our analysis identified the SUV TLR with the highest diagnostic accuracy; however, our results showed an aortic SUV max (cut-off 6.45) and an SUV TBR with almost equally high sensitivity and specificity ( Figure 2 D, Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study has shown that the presence of positive (defined as follows: visual uptake of grade two or four and/or a short axis diameter > 10 mm on LDCT) locoregional lymph nodes on [ 18 F]FDG-PET/CT imaging has a high specificity (96%) and positive predictive value (95%) for VGEI [ 25 ]. However, these findings were accompanied by a low sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The capacities of 18F-FDG-PET/CT beyond the actual body of a potentially infected graft are currently being explored and the role of abnormal locoregional lymph nodes in the diagnosis considered. According to van Rijsewijk et al, detection of abnormal nodes has a high specificity and positive predictive value for VGEI thus producing additional relevant information that might be incorporated as part of diagnostic criteria in the future [ 44 ].
Fig.
…”
Section: Diagnosismentioning
confidence: 99%